If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6b-11=-7b
We move all terms to the left:
-6b-11-(-7b)=0
We get rid of parentheses
-6b+7b-11=0
We add all the numbers together, and all the variables
b-11=0
We move all terms containing b to the left, all other terms to the right
b=11
| -54=6m | | 3(a+4)-5(a-2=22 | | 6p+37=17 | | (70×1.29×10)-(40+(70×0.18)+x=12 | | (x+2)^2+11=27 | | 3(p-4)-2p=31 | | -16+19n=15n+20 | | -3x+4=5(2x-7) | | 3x+2-x+5=19-4x | | 2x2+3x+18=0 | | -1.5x=14+x | | q4+ 15=19 | | 5x+35=3(3x-3) | | -7(x-11)=-140 | | (9x+19)=(5x-7) | | 9x-7=-9+15x | | 65-5x=0 | | .9x+15=x | | -14p+20=-2p-18-14p | | 4+2m=7 | | 45+43+4t=180 | | 9x-15-2x=-61+9x | | 1.8x-16.3=19x+13.3 | | 34+104+14v=180 | | 34+104+14v=189 | | 14-2x=3x-7-2x | | -6x+10=-8x+12 | | 90+14y+16y=180 | | -8-q=8q+10 | | 18x+2=15x+7 | | 5x^2+185x=0 | | 13-7m=32 |